2019
DOI: 10.1073/pnas.1808675116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical diffraction reveals the role of passive dynamics in a slithering snake

Abstract: Limbless animals like snakes inhabit most terrestrial environments, generating thrust to overcome drag on the elongate body via contacts with heterogeneities. The complex body postures of some snakes and the unknown physics of most terrestrial materials frustrates understanding of strategies for effective locomotion. As a result, little is known about how limbless animals contend with unplanned obstacle contacts. We studied a desert snake, Chionactis occipitalis, which uses a stereotyped head-to-tail traveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…Previous work found that generalist snakes chose self-deformations in response to available environmental forces [6, 27], a strategy which we might expect would be useful on challenging, deformable materials like GM. However, we previously found evidence that C. occipitalis does not change its waveform when faced with changes to the surroundings [29] and our robot was executing predetermined waveforms. The ability to sense and respond to induced changes in the substrate is apparently unnecessary given the initial selection of an appropriate pattern of self-deformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work found that generalist snakes chose self-deformations in response to available environmental forces [6, 27], a strategy which we might expect would be useful on challenging, deformable materials like GM. However, we previously found evidence that C. occipitalis does not change its waveform when faced with changes to the surroundings [29] and our robot was executing predetermined waveforms. The ability to sense and respond to induced changes in the substrate is apparently unnecessary given the initial selection of an appropriate pattern of self-deformation.…”
Section: Discussionmentioning
confidence: 99%
“…We used nine individuals collected from the desert in Arizona, USA (Appendix B). These sand-specialists are a consummate example of a successful strategy for moving across material with memory; they use a stereotyped waveform ([21], [29]) to quickly traverse many body lengths across the sand with little slipping of the body, leaving behind distinct tracks [31].…”
Section: Performance Of Limbless Locomotors On Granular Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…See more detail of the interpolation method in (Mitchel et al 2020). We compared interpolation accuracy of our method to B-spline, a commonly used geometric interpolation method (Fontaine et al 2008;Padmanabhan et al 2012;Sharpe et al 2015;Socha et al 2018;Schiebel et al 2019), using the dataset of kingsnake traversing a large step We challenged the robot to traverse a high friction step obstacle with increasingly large step height, H = 31, 36, 38, and 40% of robot length L. Using the partitioned gait combining lateral oscillation with cantilevering from the snake, the robot rapidly traversed a step of height H = 31%…”
Section: Continuous Body 3-d Interpolationmentioning
confidence: 99%
“…A NIMALS often use limb and body contact to negotiate complex, cluttered environments. Snakes can use their body segments to push against grass stems to change their direction of movement [1], [2]. Cockroaches have been found to use different pitch and roll body angles to traverse dense, tall grass-like barriers of varying stiffness [3], [4].…”
Section: Introductionmentioning
confidence: 99%